2020
DOI: 10.1093/jbcr/iraa091
|View full text |Cite
|
Sign up to set email alerts
|

Complete Blood Count and Derived Indices: Evolution Pattern and Prognostic Value in Adult Burned Patients

Abstract: Certain parameters of complete blood count (CBC) such as red cell distribution width (RDW) and mean platelet volume, as well as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and RDW-to-platelet ratio (RPR) have been associated with inflammatory status and outcome in diverse medical conditions. The aim of this study was to describe the evolution pattern of these parameters in adult burned patients. Adult burned patients admitted to the National Burn Center in Uruguay between May 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 36 publications
1
25
1
2
Order By: Relevance
“…Clinical laboratory results such as creatinine, platelet count, PT, and PLR are significant risk factors in burn patients. This result is consistent with previous studies using classic logistic regression analysis [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Clinical laboratory results such as creatinine, platelet count, PT, and PLR are significant risk factors in burn patients. This result is consistent with previous studies using classic logistic regression analysis [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…CBC is a routinely applied laboratory blood test for most patients. The unique components analyzed by CBC are known to be related with inflammation or infection that affects the prognosis of medical conditions [ 24 ]. Of these simple blood biomarkers, RDW is a numerical measurement of the range in the volume and size of the erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Simple and easily available biomarkers are more popular and accepted by clinicians ( 34 ). PPR, the ratio of PDW to PLT, is derived from CBC parameters ( 35 ). PPR was a simple and cheap parameter, which could be evaluated in routine clinical practice with minimal additional cost, and could help clinicians quickly identify high-risk patients ( 26 , 29 , 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…They found that the AUC of RPR for adverse outcome prediction on day 3 were 0.712, while 0.750 on day 7. Angulo M et al ( 35 ) found that neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and RPR in the early stage of severe burns could identify patients with increased mortality. In our study, the AUC of PPR for predicting 120-day mortality was 0.816 on day 3, while 0.750 on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…RPR has been associated with various clinical conditions in medical literature. These conditions include rheumatoid arthritis, autoimmune hepatitis, cardiovascular morbidities, mortality of burned patients and acute pancreatitis [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%